Nasofarinks karsinoom : behandelingsresultate met gekombineerde terapie - De Villiers, E. H.(Etienne Hugo) (Stellenbosch : Stellenbosch University, 2012)
Study project (M.Med.) -- University of Stellenbosch, 1998.